Transparansi dan Partisipasi Publik dalam Rekrutmen Calon Hakim Konstitusi - Wijayanti, Winda; Quraini M, Nuzul; Putri R, Siswantana (Jurnal Konstitusi, 2015)
Recruitment is not an arena ofÂ  â€œhazingâ€Â  andÂ  theÂ  additionÂ  ofÂ  bureaucracyÂ  but a forum to explore the nature of integrity, capability, and independence of the candidates for constitutional judges. The process of recruiting candidates for constitutional judges to choose the recruitment system based on the principle of transparency, participatory, objective, and accountability to the people of the early stages and mechanisms of recruitment until the determination of the constitutional judges candidates that can lead to public confidence and form of democracy because of the position of the control and balance between state with people. Thus, the recruitment process needs to be accompanied by a written rule that can evolve as needed to create the best candidates for constitutional judges based recruitment process by filing recruitment agency and SOP (Standard Operational of Procedure). The problem is not on the persons making the recruitment, agency nominate candidates for judge, and the lack of setting the terms of the constitutional judge best candidate, but the choice of constitutional judges are recruited to promote open to the public process. DPR as one of the agency of the state to file a constitutional justice through the recruitment team can choose the right man in the right position through the selection of recruitment mechanism in accordance with the constitutional.